2017
DOI: 10.1016/j.colsurfb.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous calcium phosphate using casein as a template: Application to bovine serum albumin sorption

Abstract: Mesoporous hydroxyapatites were synthesized at room temperature using casein as a template, and key experimental factors, such as casein concentration, pH and extraction of casein in the final solids by washing and thermal treatment, were systematically investigated. The X-Ray Diffraction (XRD) patterns confirmed the synthesis of well-crystallized hydroxyapatite. The N adsorption/desorption isotherms were in agreement with the formation of mesoporous hydroxyapatite with a maximum surface area of 106mg. Infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 59 publications
3
16
0
Order By: Relevance
“…Mesostructured phosphates have been extensively studied for their unique properties and great potential applications, particularly in biomedicine and catalysis. [10][11][12][13][14][15][16][17][18] However, although various mesoporous phosphates have been documented in the literature, their synthesis is still fraught by several problems and limitations. Present strategies for the synthesis of mesoporous phosphates are based largely on the use of organic templates.…”
Section: A New Strategy For Synthesizing Mesoporous Phosphatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesostructured phosphates have been extensively studied for their unique properties and great potential applications, particularly in biomedicine and catalysis. [10][11][12][13][14][15][16][17][18] However, although various mesoporous phosphates have been documented in the literature, their synthesis is still fraught by several problems and limitations. Present strategies for the synthesis of mesoporous phosphates are based largely on the use of organic templates.…”
Section: A New Strategy For Synthesizing Mesoporous Phosphatesmentioning
confidence: 99%
“…Among the various non-siliceous mesoporous materials, mesoporous phosphates are gaining increasing attention, especially because of their high potential for applications in biomedicine and catalysis. Mesoporous phosphates are highly bioactive and biocompatible, [10][11][12][13][14] the two most important pre-requisites for applications in drug delivery systems or bone tissue engineering. Moreover, the facile functionalization of PO 4 and/or P-OH groups through organic or inorganic molecules could offer versatile options for tailoring their surface properties.…”
Section: Introductionmentioning
confidence: 99%
“…The literature mentions different substances used as a template [18][19][20][21][22][23][24][25]40 which aims to improve some properties of the material, changing its morphology, increasing the specific surface area and pore size, and also decreasing the particle size. Some additives/templates used, such as surfactants, may have elements that can be difficult to remove, contaminating the biomaterial.…”
Section: Textural Characterizationmentioning
confidence: 99%
“…These additives, also called templates, can be polymers, surfactants, and biomolecules [17][18][19][20][21][22][23][24][25] that assist in the control and changes of material properties. The literature reports that the use of substances such as caffeine, starch, vitamin C, albumin, gelatin 18,[23][24][25] as templates/additives affect the physico-chemical properties of the HAp particles. The use of sucrose has been widely reported for studies related to the formation of porous scaffolds 26 However, there are studies that aim the synthesis of other materials, such as that carried out by Sabbaghan et al 27 who reported the use of sucrose for the synthesis of ZnO nanoparticles, motivating its use as a template in the synthesis of HAp.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, biogenic materials are utilized as sacrificial template due to the small size, homogeneity, periodic structures, and abundance in nature. Porous tricalcium phosphate was prepared by utilizing protein as templates [39,40]. Similarly, CeO 2 catalyst or nanosized NiO could be synthesized through sacrificial template of albumin [41,42].…”
Section: Introductionmentioning
confidence: 99%